2020
DOI: 10.1093/gji/ggaa359
|View full text |Cite
|
Sign up to set email alerts
|

Performance of three iGrav superconducting gravity meters before and after transport to remote monitoring sites

Abstract: Summary High spatial and temporal resolution of gravity observations allows quantifying and understanding mass changes in volcanoes, geothermal or other complex geosystems. For this purpose, accurate gravity meters are required. However, transport of the gravity meters to remote study areas may affect the instrument's performance. In this work, we analyse the continuous measurements of three iGrav superconducting gravity meters (iGrav006, iGrav015 and iGrav032), before and after transport betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In addition to environmental gravity contributions, artefacts of the gravity meter like instrumental drift or self-noise may decrease the accuracy of the target signal (Crossley et al 2004;Rosat and Hinderer 2018). With respect to long-term drift rates, Schäfer et al (2020) showed the impact of transporting a superconducting gravimeter. Therefore, an accurate estimation and reduction of instrumental drift and environmental contributions is essential before we can interpret the gravity residuals accurately with respect to a specific geophysical phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to environmental gravity contributions, artefacts of the gravity meter like instrumental drift or self-noise may decrease the accuracy of the target signal (Crossley et al 2004;Rosat and Hinderer 2018). With respect to long-term drift rates, Schäfer et al (2020) showed the impact of transporting a superconducting gravimeter. Therefore, an accurate estimation and reduction of instrumental drift and environmental contributions is essential before we can interpret the gravity residuals accurately with respect to a specific geophysical phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…5 we compare the time series of gravity residuals of iGrav006, iGrav015 and iGrav032, before and after the combined environmental reductions of global effects, soil water content, snow water equivalent and vertical surface displacement. The initial residuals (before the aforementioned environmental reductions were applied) have been derived by reducing Earth and ocean tides, polar motion, local pressure and instrumental drift, as well as removing spikes and offsets (caused by earthquakes and other disturbances) from the original gravity time series (Schäfer et al 2020). Reductions of the individual environmental gravity contributions for each iGrav are shown in Figures A5 to A7 in the Appendix.…”
Section: Gravity Residualsmentioning
confidence: 99%
“…In addition to environmental gravity contributions, artefacts of the gravity meter like instrumental drift or self-noise may decrease the accuracy of the target signal (Crossley et al 2004;Rosat and Hinderer 2018). With respect to long-term drift rates, Schäfer et al (2020) showed the impact of transporting a superconducting gravimeter. Therefore, an accurate estimation and reduction of instrumental drift and environmental contributions is essential before we can interpret the gravity residuals accurately with respect to a speci c geophysical phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gravimetric methods are already applied in the RCZ. Episodic AG observations were carried out since 2004 with a FG5 absolute gravimeters by the Leibniz University Hannover (LUH) for the analysis of long-term gravity changes at Mount Zugspitze and for a long-range gravimeter calibration base (Timmen et al, 2006;Peters et al, 2009). Timmen et al (2021) estimated a geophysical trend of −20 nm s −2 yr −1 , with an uncertainty of 3 nm s −2 yr −1 (single standard deviation 1σ ) from AG observations between 2004 and 2019 as a consequence of alpine mountain uplift and hydrological mass loss.…”
mentioning
confidence: 99%